Association Between Chronic Obstructive Pulmonary Disease and Mortality in Participants with Arthritis: Data from the National Health and Nutrition Examination Survey 1999–2018 - Zhang, Yingying; Chen, Guangxi; Huang, Aixia; Hu, Ying; Fu, Chengfeng (Chronic obstructive pulmonary diseases, 2025)
Chronic obstructive pulmonary disease (COPD) is closely associated with arthritis. This study aims to evaluate the correlation between COPD and mortality among participants with arthritis. The study included 11,298 participants from the National Health and Nutrition Examination Survey (NHANES) 1999-2018, who self-reported having arthritis. Cox proportional hazard models were used to assess the association between COPD and mortality among participants with arthritis. Kaplan-Meier survival curves were plotted to compare survival probabilities between groups. Subgroup and sensitivity analyses were conducted to assess the robustness of the results. During an average follow-up of 8.8 years, 3061 all-cause deaths were observed, including 1024 related to cardiovascular disease (CVD). After weighted multivariable adjustment, COPD was found to be significantly associated with both all-cause and CVD mortality among these arthritis participants. The hazard ratio (HR) for all-cause mortality among arthritis patients with COPD was 1.41 (95% confidence interval [CI]: 1.25-1.60, < 0.001), and the HR for CVD mortality was 1.29 (95% CI: 1.08-1.53, < 0.001). Kaplan-Meier survival curves attributed higher rates of both all-cause and CVD mortality among participants with COPD compared to those without (log-rank test, < 0.001). Additionally, COPD increased the risk of both chronic lower respiratory disease (CLRD) mortality (HR 5.46, 95% CI: 3.48-8.56, < 0.001) and non-CLRD mortality (HR 1.24, 95% CI: 1.07-1.44, =0.004). In the American population, arthritis patients with COPD have higher risks of all-cause and CVD mortality compared to those without COPD.